The Moderating Role of Liquidity on Capital Structure and Profitability: A Study on Indonesian Transportation Subsector - Akhmadi Akhmadi; Enis Khaerunnisa; Ida Asiah Nurfitriyani (Faculty of Economics, Universitas Sriwijaya, 2023)
This research analyses the impact of capital structure on profitability, considering liquidity as a moderating variable. Furthermore, it is focused on transportation sub-sector companies listed on the Indonesia Stock Exchange from 2012 to 2020. A causalcomparative research method is employed, with hypothesis testing is conducted for a moderating regression. To ensure the accuracy of the findings, a purposive sampling technique is utilised, resulting in 198 firm-year observations which represented by 22 listed firms. The study's findings indicate that capital structure has no bearing on profitability. The analysis's findings indicate that the liquidity ratio, which acts as a moderating variable, significantly affect for the relationship between capital structure and profitability. The capital structure further strengthens the increase in profitability if it is supported by the company's liquid current assets.